Bringing agroecology to scale: key drivers and emblematic cases. Issue 6 (3rd July 2018) - Mier y Terán Giménez Cacho, Mateo; Giraldo, Omar Felipe; Aldasoro, Miriam; Morales, Helda; Ferguson, Bruce G.; Rosset, Peter; Khadse, Ashlesha; Campos, Carmen
ABSTRACT: Agroecology as a transformative movement has gained momentum in many countries worldwide. In several cases, the implementation of agroecological practices has grown beyond isolated, local experiences to be employed by ever-greater numbers of families and communities over ever-larger territories and to engage more people in the processing, distribution, and consumption of agroecologically produced food. To understand the nonlinear, multidimensional processes that have enabled and impelled the bringing to scale of agroecology, we review and analyze emblematic cases that include the farmer-to-farmer movement in Central America; the national peasant agroecology movement in Cuba; the organic coffee boom in Chiapas, Mexico; the spread of Zero Budget Natural Farming in Karnataka, India; and the agroecological farmer–consumer marketing network " Rede Ecovida, " in Brazil. On the basis of our analysis, we identify eight key drivers of the process of taking agroecology to scale: (1) recognition of a crisis that motivates the search for alternatives, (2) social organization, (3) constructivist learning processes, (4) effective agroecological practices, (5) mobilizing discourses, (6) external allies, (7) favorable markets, and (8) favorable policies. This initial analysis shows that organization and social fabric are the growth media on which agroecology advances, with the help of the other drivers. A more detailed understanding is needed on how these multiple dimensions interact with, reinforce, and generate positive feedback with each other to make agroecology's territorial expansion possible.